2010
DOI: 10.1128/aac.00059-10
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of a Photosensitizer to Aggregatibacter actinomycetemcomitans Biofilm

Abstract: The ability to selectively target specific biofilm species with antimicrobials would enable control over biofilm consortium composition, with medical applications in treatment of infections on mucosal surfaces that are colonized by a mixture of beneficial and pathogenic microorganisms. We functionalized a genetically engineered multimeric protein with both a targeting moiety (biotin) and either a fluorophore or a photosensitizer (SnCe6). Biofilm microcolonies of Aggregatibacter actinomycetemcomitans, a periodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…This fact could be responsible for biofilm resistance to PDI when compared with their planktonic counterparts. In an attempt to overcome this problem, investigations into the use of chlorin e6 for antibacterial PDI have frequently used chlorin conjugates to increase phototoxicity towards biofilms (Soukos et al 2003;Garcez et al 2007;Suci et al 2010). The difficulty of PS in penetration into the inner layers of biofilms may also be explained by the possibility of aggregate formations at high concentrations of the PS.…”
Section: Discussionmentioning
confidence: 97%
“…This fact could be responsible for biofilm resistance to PDI when compared with their planktonic counterparts. In an attempt to overcome this problem, investigations into the use of chlorin e6 for antibacterial PDI have frequently used chlorin conjugates to increase phototoxicity towards biofilms (Soukos et al 2003;Garcez et al 2007;Suci et al 2010). The difficulty of PS in penetration into the inner layers of biofilms may also be explained by the possibility of aggregate formations at high concentrations of the PS.…”
Section: Discussionmentioning
confidence: 97%
“…Media for culturing Aa consisted of modified tryptic soy broth (MTSB; Suci et al 2010). Frozen stocks were maintained at −80°C in 20% glycerol, 80% MTSB.…”
Section: Methodsmentioning
confidence: 99%
“…Although it has been shown that E. coli overexpressing the Hb receptor of P. gingivalis binds both Cu- and Zn-PPIX with similar affinity as Fe-PPIX, their remains no direct evidence for active transport of noniron porphyrins into the periplasm (Olczak, Dixon, & Genco, 2001). Despite promising early studies on the OM heme receptors as Trojan horses in delivering noniron metalloporphyrin antibacterials, most of the current focus has been directed at utilizing the photodynamic properties of light-activated Sn-chlorins as antibacterials (Embleton et al, 2002, 2005; Suci, Kang, Gmur, Douglas, & Young, 2010). …”
Section: Heme Uptake and Utilization In Antimicrobial Drug Developmentioning
confidence: 99%